Public awareness and attitudes toward biobank and sample donation: A regional Chinese survey - Gao, Zhaolin; Huang, Yanxia; Yao, Fei; Zhou, Ziyu (Frontiers in Public Health, 2022)
Background The biobank is an extraordinary aid to research and scientific progress. Public involvement in biobanks, necessary for their development, is limited due to inadequate knowledge of biobanking and concerns about sample donation. This study explores the effectiveness of different publicity methods in improving participants' willingness to donate, and assesses public motivations and concerns. It aims to identify an efficient method of improving participants' awareness of biobanking and promoting sample donation. Methods A structured 20-item questionnaire was formulated to evaluate participants' knowledge of and attitudes toward biobanks and sample donation. In total, 1,500 questionnaires were disseminated to three groups of 500 participants who received, respectively, picture-based promotional material, text-based promotional material, or who attended a biobank-related lecture. Of these, 945 completed questionnaires were received. All the participants completed the questionnaires twice, before and after the corresponding publicity education. Results After each of the three methods of publicity based on text, pictures and a lecture, respondents' willingness to donate samples was significantly increased (P < 0.001), the lecture being more effective than the other two methods (P = 0.001). Participants with a medical background were more willing to donate biospecimens after publicity than those without medical backgrounds (P < 0.005) but had common motivations for donation including altruism and aiding medical research. The main concern hindering respondents' willingness to donate was the security of personal information. Conclusion Different types of biobank-related publicity based on text material, pictorial material and a lecture all improved respondents' willingness to donate and reduced concerns regarding sample donation. Medical background was a critical factor affecting attitudes toward sample donation after publicity. The results of this study suggest strategies that may popularize biobanks and enhance sample donation, further promoting the development of biobanks.